Sino-US Cultural Differences, Academic Integration, and Learning Outcomes among Chinese International Students - Jiarui Tian (Lecture Notes in Education Psychology and Public Media, 2026)
The number of Chinese international students in the United States has stayed high. They face various challenges in personal and academic life, one of which is cultural adaptation to the stark differences between Chinese and American cultures. This study explores how Sino-US cultural differences influence students' social willingness and subsequent academic performance with a literature review based on findings in existing studies. Based on multiple studies from credible sources, this study is deliberately designed to cast light on not only key dimensions of cultural differences but also students' adaptation strategies with a focus on how their social willingness mediates their academic integration. The findings suggest that Chinese international students are susceptible to collectivism, high-context communication and face culture in Chinese culture, which suppress their cross-cultural social willingness because American individualism and low-context communication encourage active social interactions. Consequently, Chinese international students in the United States often remain silent in class and avoid seeking academic help, which form a vicious cycle; however, peer social support can buffer this negative effect. This study concludes that enhancing cross-cultural social willingness can make a significant difference to Chinese students' academic success in the United States.